The economic performance of public investments: an ex post evaluation of water resources investments - Haveman, Robert H. (Baltimore, Published for Resources for the Future by the Johns Hopkins Press, 1972)
This study is an exploratory effort to develop the techniques of ex post evaluation of water resources development activities.
Includes bibliographical references.
osc 31/01/2019
Loans
Keywords: Water resources development; United States